SOLID STATE CHARACTERIZATION AND QUANTIFICATION OF ABACAVIR SULPHATE, LAMIVUDINE AND ZIDOVUDINE AND ITS TABLET FORMULATION BY X-RAY POWDER DIFFRACTION METHOD - Rajasekaran, Aiyalu; Sunkara, Manasvi (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To determine simultaneously the content of crystallinity of Abacavir sulphate (ABC), Lamivudine (LMD) and Zidovudine (ZVD) using X-ray Powder Diffraction (XRPD) technique and to validate the developed analytical methods and to statistically perform correlations by ANOVA technique. Methods: Characteristic non-interfering peaks of ABC, LMD and ZVD were identified by using X-Ray Powder Diffraction method for assessment of the content of crystallinity. Results: A working range 70 % to 130 % was taken for the establishment of linearity of the ABC, LMD and ZVD in the formulation and the coefficient of regression of ABC was 0.999, LMD was 0.998 and ZVD was 0.998. The F value by ANOVA was found to be within limits and satisfactory. Conclusion: The developed method was adapted to the samples exposed to 40 Â°C/75 % RH, accelerated stability conditions and hence proved that it can be used for monitoring real-time samples. Keywords: Abacavir sulphate, Lamivudine, Zidovudine, Crystallinity, XRPD, Validation